Cis‐Clerodane Diterpenoids with Structural Diversity and Anti‐inflammatory Activity from Tinospora crispa. Issue 24 (22nd October 2022) - You, Jin‐Qiu; Liu, Yi‐Nan; Zhou, Jun‐Su; Sun, Xin‐Yu; Lei, Chun; Mu, Qing; Li, Jing‐Ya; Hou, Ai‐Jun
Comprehensive Summary: Twelve new cis ‐clerodane diterpenoids, designated as crispinoids A—L (1 —12 ), together with three known analogues (13 —15 ), were isolated from Tinospora crispa . Their structures were fully assigned by comprehensive spectroscopic techniques, single‐crystal X‐ray diffraction experiments, and electronic circular dichroism (ECD) analyses. The isolated clerodanes displayed diverse heterocyclic frameworks including 6/6/6‐, 6/5/6/6‐, 6/6/5‐, 6/6‐, and 6/5/6‐fused ring systems. Some of the isolates showed ATP‐citrate lyase (ACLY) and nuclear factor kappa B (NF‐ κ B) pathway inhibition. The NF‐ κ B inhibitors further suppressed the lipopolysaccharide (LPS)‐induced inflammatory responses in RAW 264.7 cells. Abstract : Twelve new cis ‐clerodane diterpenoids, crispinoids A—L (1 —12 ), and three known analogues (13 —15 ), were isolated from Tinospora crispa . The isolated clerodanes displayed diverse heterocyclic frameworks. Some of the isolates exhibited ACLY and NF‐ κ B pathway inhibitory activities. The NF‐ κ B inhibitors further suppressed the lipopolysaccharide (LPS)‐induced inflammatory responses in RAW 264.7 cells.